F02 Selisistat: soluble HTT protein levels as a potential pharmacodynamic readout. (29th August 2012) - Westerberg, G; Massai, L; Magnoni, L; Pollio, G; Tripepi, G; Diodato, E; Caricasole, A; Bernocco, S; Tabrizi, SJ; Landwehrmeyer, B; ,
Abstract : Background: Siena Biotech SpA is developing selisistat (SEN0014196) as a potentially disease-modifying therapy for HD. Selsistat is a potent and selective SirT1 inhibitor (IC50 98 nM) that has shown benefit across a range of preclinical models for HD, from cells and neurons infected with mutant huntingtin to transgenic Drosophila and R6/2 mice. The compound has shown to be safe and well tolerated in healthy volunteers and with a favourable pharmacokinetic profile. Aim: To develop a sensitive and quantitative (ELISA-based) readout for the detection of total soluble HTT protein in biological matrices, and to investigate the effects of selisistat on HTT protein levels in Peripheral Blood Mononuclear Cells (PBMC) samples deriving from a Phase 1B study in HD patients. Methods: This assay is based on a sandwich ELISA format and uses an electrochemiluminescent read-out to quantify the HTT protein level in PBMC extracts. The PBMCs are lysed by sonication and extracted by centrifugation. The supernatant is applied to a streptavidin-coated MSD plate which has been previously treated by addition of a biotinylated anti-mouse antibody followed by a mouse monoclonal anti HTT (1844–2131 aa) antibody. After incubation, bound HTT is detected using a rabbit anti-HTT (513–590 aa) secondary antibody followed by a Sulfotag conjugated anti-rabbit detection antibody. The signal is quantified by adding MSD read buffer and reading using the Meso Scale Discovery Sector Imager. Results and Conclusions: The effects of two dose levels of selisistat and placebo on total soluble HTT levels in PBMC samples from HD patients in a 14-day Phase1B study will be presented.